THE PROBLEM OF EXISTENCE OF VIRTUAL OBJECTS FROM THE PHILOSOPHICAL PERSPECTIVE. - Mazurek, Mariusz (Filozofia i Nauka)
I consider the problem of existence of virtual objects, mainly their mode of existence, while omitting the issue of the criteria of their existence. I present and analyze the concepts of modes (forms, kinds) of existence of virtual objects proposed in the literature of the subject, and then I demonstrate my own position on the issue. My position on the existence of virtual objects has certain points coinciding with the already postulated views, but at the same time it differs from them in some basic aspects. In my view virtual objects are “born” in human individual consciousness as the objects of specific creative states of the mind. So initially they are private objects belonging to the individual subjective sphere. However, their final and ready forms emerge in complex processes of objectifying and autonomizing the respective private conscious states and their objects. In these processes the private objects are transformed into objects intersubjectively accessible and existing in the collective cultural sphere. In both their forms, initial and final, virtual objects are non-material entities: first subjective, then objective. The ontic status of virtual objects is very similar to the status of intangible ideas and all the non-material objects created by the human mind. The main difference consists in that virtual objects are expressed by the use computers programmes, while other non-material objects created by human beings are expressed by use of words, pictures, literature and art works, etc.